Comprehensive policy evaluation of NEV development in China, Japan, the United States, and Germany based on the AHP-EW model. (20th March 2019) - Ma, Ye; Shi, Tianyu; Zhang, Wei; Hao, Yu; Huang, Junbing; Lin, Yinan
Abstract: As pressure on resources and the environment continues to intensify, the development of the automobile industry must maintain its momentum. At the same time, the demand for the transition of the national economy to a more sustainable style is increasing. Under such circumstances, the new energy vehicle industry has drawn increasing attention in China and abroad. This nascent industry requires supportive policies from the government for its success. The purpose of this study is to compare the similarities and differences of new energy vehicle-related policies for developing new energy vehicles in China, Japan, Germany, and the United States (U.S.). Based on the analytic hierarchy process-entropy weight method (i.e., AHP-EW model), a combination of subjectivity and objectivity, we adopt a quantitative method to appraise the new energy vehicle development situation in these four countries with a series of indexes, such as technological innovation, market development status, and infrastructure construction level. The results show that Germany is the strongest in terms of comprehensive measurements, followed by China, the U.S., and Japan. In this ranking, the U.S. shows the strongest technological innovation abilities; China is number one in marketing; and Japan is first in infrastructure construction.